Hubungan Faktor Individu dan Faktor Pekerjaan terhadap Keluhan Musculoskeletal Disorders pada Pegawai - Putri Tika Rahayu; Marina Ery Setyawati; Cahya Arbitera; Afif Amir Amrullah (Politeknik Kesehatan Tanjung Karang, 2020)
Musculoskeletal disorders are work-related diseases and conditions that are not safe and uncomfortable, almost all employees have experienced the disorders, ranging from pain in the neck, shoulders, and lower back. This study was conducted to determine the relationship of individual factors and work factors to complaints of musculoskeletal disorders in employees at the Ministry of Health’s Republic of Indonesia Civil Service Bureau in 2020. This study used a cross-sectional study design with the Purposive Sampling technique, with a sample of 103 employees. The research instruments used in the study were the questionnaire regarding individual characteristics, Rapid Office Strain Assessment (ROSA), Nordic Body Map (NBP), and Global Physical Activity Questionnaire (GPAQ) questionnaire. The result of this study indicates that the variables related to complaints of musculoskeletal disorders are age (p-value=0,001), work period (p-value=0,001), and work posture (p-value=0,001), while gender, BMI, physical activity, duration of the word are not related to complaints of musculoskeletal disorders. Employees must do physical activity 3 times a week, need to reorganize the design of the workplace so it can reduce the presence of awkward posture, and pay more attention to the position of the body at work.